Righteousness, Ideology and the Kingdom of God in Matthew 6:10 - A reading of Identity Politics from Matthew’s Lord’s Prayer - Fednand Manjewa M’bwangi (Pharos Journal of Theology, 2020)
A number of New Testament Scholars contend that Matthew’s emphasis for God’s Kingdom in the Lord’s Prayer either implores God to establish His empire on earth, or stands as a catalyst for character formation, or even presents a more interactive perspective of God. In spite of observing Matthew’s focus on God’s work on earth, these scholars fail to see the connection between Matthew’s concept of righteousness, his ideology and the phrase “your Kingdom come” (Matt 6:10, RSV). The aim of this article is to argue that Matthew rhetorically employs his concept of “your Kingdom come” to elaborate the ideological significance of righteousness in advancing identity politics.